Effect of umbilical cord-mesenchymal stem cells on skin tensile strength in pressure ulcers: a rat model study - Aulia, Indri; Dilogo, Ismail Hadisoebroto; Prasetyono, Theddeus Octavianus Hari; Pawitan, Jeanne Adiwinata; Kekalih, Aria; Siregar, Nurjati Chairani; Whulanza, Yudan; Hasibuan, Lisa (Medical Journal of Indonesia, 2026)
BACKGROUND Stem cell therapy has emerged as a promising alternative for the management of chronic wounds, including pressure ulcers. Tensile strength, which reflects the biomechanical integrity of the skin, serves as an objective measure of wound healing. This study aimed to evaluate the effect of locally administered umbilical cord-mesenchymal stem cells (UC-MSCs) on the tensile strength of healing 3rd-degree pressure ulcers in a Sprague Dawley rat model. METHODS 21 adult male Sprague Dawley rats were divided into 3 groups: normal rats without ulcers, untreated pressure ulcer as control, and pressure ulcers treated with UC-MSCs. The treatment group received locally injected 4 × 10⁶ UC-MSCs at the ulcer site. On day-21, the tensile strength parameters (rupture point, elongation at break, and elastic modulus) of the dorsal skin were assessed using the Universal Testing System. RESULTS When expressed relative to normal skin tensile strength, the UC-MSC group exhibited higher tensile parameters that were higher than the controls by 2.08% for rupture point, 3.29% for elongation at break, and 8.42% for elastic modulus. Although these differences between the UC-MSCs and control groups across all tensile strength parameters were not statistically significant, a clear trend toward improved tensile strength parameters were observed in the UC-MSCs group. CONCLUSIONS Local UC-MSCs administration showed a consistent trend toward improved tensile strength in healing 3rd-degree pressure ulcers, albeit without statistically significant differences compared to controls. These findings support the further exploration of UC-MSCs as a potential treatment for promoting biomechanical restoration in healing pressure ulcers.